2018
DOI: 10.1007/s12008-018-0458-8
|View full text |Cite
|
Sign up to set email alerts
|

3D interactive environment for the design of medical devices

Abstract: The effectiveness of custom-made prostheses or orthoses heavily depends on the experience and skills of the personnel involved in their production. For complex devices, such as lower limb prosthesis, a conventional manual approach affects the process at the point that the result is frequently not acceptable at the first trial. The paper presents a computer-aided environment, named socket modelling assistant 2 (i.e., SMA 2 ), to interactively design the socket of lower limb prosthesis by implementing a set of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
(36 reference statements)
0
19
0
1
Order By: Relevance
“…However, previous research showed that the quality of these prosthetic sockets was at the lower end of the acceptance level [16À18,46]. Because the positive mold is adjusted manually in the process of PTB sockets, the socket shape is highly dependent on the experience and skills of the prosthetist, with the consequence that quality assurance cannot be given [15][16][17][18].…”
Section: Comparison With the Standard For Lmicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous research showed that the quality of these prosthetic sockets was at the lower end of the acceptance level [16À18,46]. Because the positive mold is adjusted manually in the process of PTB sockets, the socket shape is highly dependent on the experience and skills of the prosthetist, with the consequence that quality assurance cannot be given [15][16][17][18].…”
Section: Comparison With the Standard For Lmicsmentioning
confidence: 99%
“…However, there are no standards for testing the prosthetic socket, because this part is custom made. Nevertheless, multiple studies have used these guidelines for testing FDM-printed prosthetic sockets, making this testing method a logical choice to test the prothesis [18,24,53,54]. In recent years, potentially suitable FDM print materials became available with increased layer-on-layer adhesion.…”
Section: Improved Socket Strengthmentioning
confidence: 99%
“…This scan generates a digital file that needs specific software for visualization and that, for the most part, can be exported in STL (Standard Triangle Language) format. However, these programs generate significant costs for orthodontists (Camardella and Vilella 2015;Burhardt et al 2016;Colombo et al 2018). On the other hand, there are free software available on the Internet that allow the visualization of digital orthodontic models since they are provided in STL format.…”
Section: Introductionmentioning
confidence: 99%
“…Portnoy et al [8] also reported that using a subject-specific real-time analysis of the internal tissue loads in the residuum is a practical tool for evaluating the internal stress inside the residuum in a clinical setting or outdoors. From another aspect, Colombo et al [9] managed to develop a computer-aided environment, namely, a socket-modeling assistant (SMA), combining knowledge from prostheses and a 3D model simulation to create a prosthesis socket. Such research has resulted in the creation of a prosthesis socket using the additive manufacturing (AM) technique, although a compatibility analysis of the created socket has yet to be carried out.…”
Section: Introductionmentioning
confidence: 99%